Career guidance in Lithuania: tradition or fear of change? - Luobikiene, I., Kaunas Univ. of Technology (Lithuania). Inst. of Public Policy and Administration (Rural Environment. Education. Personality. (REEP). Proceedings of the International Scientific Conference (Latvia), 2015)
Career guidance has a long tradition in Lithuania that includes basic formal and non-formal education elements and levels and provides its fundamentals at secondary education institutions. In Soviet times, also, to a certain extent – nowadays, career guidance is more associated with students' achievements rather than the demand of specialists in the labour market. Although the integration of graduates into the labour market is a "hot" subject for scientists, practitioners, experts in the field at various levels, however, so far, there has been a tendency in Lithuania to educate traditionally popular (such as lawyers, economists), though excessively surplus in the labour market, specialists. This justifies the relevance of the topic and the aim of this article to investigate what actually determines – tradition or fear of change – which the career guidance system fails to respond flexibly to the needs of the Lithuanian labour market. The research methods employed are the analysis of scientific literature and legal acts, and secondary data analysis.